2011
DOI: 10.1007/s00520-011-1243-4
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient oncology rehabilitation in Toronto: a descriptive 18-month retrospective record review

Abstract: In this sample, the majority of patients were older women, and many lived alone. While the group as a whole made significant functional gains, those who were younger improved more. Having a diagnosis of uterine or brain cancer was associated with lower functional change scores. This study was limited by a small sample size and the retrospective design; however, the results provide a foundation for future prospective research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…We first demonstrated that physical therapy increased the FIM score in patients with HCC. In previous studies, physical therapy has been reported to increase the FIM score in patients with various cancers, including colorectal cancer [10] and pancreatic cancer [36]. Thus, our results are in good agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…We first demonstrated that physical therapy increased the FIM score in patients with HCC. In previous studies, physical therapy has been reported to increase the FIM score in patients with various cancers, including colorectal cancer [10] and pancreatic cancer [36]. Thus, our results are in good agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…A need for rehabilitative care and an improvement in the QOL after rehabilitation was also observed in older colon cancer patients [31]. The findings of positive changes in physical health are consistent with findings from other studies that investigated somatic status [33,46], functional status [47], and QOL [48] in rehabilitants with various cancers. The two included RT investigated shortterm physiological adaption following different aerobic exercise intensities [41,42].…”
Section: Summary Of Study Findings and Comparison To Previous Studiessupporting
confidence: 87%
“…For instance, five studies collapsed analyses and presented results across all patient groups, which were diverse and included all cancer patients in rehabilitation 39 , all inpatient rehabilitation 40 , all neurologic rehabilitation patients 41 , all patients in states of severely altered consciousness 42 , and all patients with disorders of consciousness 43 . Furthermore, two studies included nTBI patients in a ‘brain dysfunction’ group 44,45 , which also included TBI.…”
Section: Discussionmentioning
confidence: 99%